Robert D. Putnam, Making Democracy Work. Civic Traditions in Modern Italy. New Jersey, Princeton University Press, 1993, 258 páginas. - Pérez Liñán, Aníbal (1997)
Fil: Pérez Liñán, Aníbal. University of Notre Dame; Estados Unidos.